2020
DOI: 10.1155/2020/3872919
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Comparison of Different Acupuncture Treatments for Functional Dyspepsia: A Systematic Review with Network Meta‐Analysis

Abstract: Background. Acupuncture has been found to be an effective treatment for functional dyspepsia (FD). Currently, several types of acupuncture have been developed but it is not clear which type is suitable for FD. Currently, doctors often rely on experience to decide which form of acupuncture to apply. Herein, we employed network meta-analysis (NMA) to compare the effectiveness of various methods of acupuncture in the treatment of functional dyspepsia. Methods. We searched for randomized controlled trials (RCTs) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 49 publications
(58 reference statements)
0
21
0
1
Order By: Relevance
“…Specifically, MA is defined as manual manipulation of needles after insertion at certain acupuncture points ( 16 ). EA is characterized by application of small current passing through acupuncture needles to produce the combined effect of electrical and needling stimulation ( 68 ). LA is a kind of non-penetrating acupuncture that uses low-power laser to stimulate acupoints ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, MA is defined as manual manipulation of needles after insertion at certain acupuncture points ( 16 ). EA is characterized by application of small current passing through acupuncture needles to produce the combined effect of electrical and needling stimulation ( 68 ). LA is a kind of non-penetrating acupuncture that uses low-power laser to stimulate acupoints ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we performed this NMA to help clinicians and researchers decide which acupuncture modality to use for PD. Although several NMA studies on acupuncture for various diseases have been reported [56][57][58], this is the first NMA study of acupuncture on PD. In our study, BEEV seems to be the best therapeutic option for motor symptoms and activities of daily living in patients with PD.…”
Section: Implications For Clinical Practice and Suggestions For Further Researchmentioning
confidence: 94%
“…[ 14 ] The clinical efficacy of acupuncture on FD has also been confirmed by a number of clinical trials, which can improve patients’ dyspepsia symptoms and is no less effective than conventional western medicine treatment. [ 15 , 16 ] Currently, there is no clinical study on acupuncture combined with Liujunzi Decoction in the treatment of FD. Therefore, we designed this randomized controlled trial to evaluate the efficacy and safety of acupuncture combined with Liujunzi decoction in the treatment of FD.…”
Section: Introductionmentioning
confidence: 99%